IMPLEMENTASI APLIKASI CANVA DALAM PEMBUATAN POSTER SEBAGAI MEDIA PEMBELAJARAN BAHASA INDONESIA KELAS XI SMAN 1 BESUK - Malikal Balgis , Dewi; Firmandil Diharjo , Roby; Ali Rahbini, Hakimah (Universitas Islam Zainul Hasan Genggong, 2025)
Technological developments have given rise to more diverse types of learning media, especially Canva media. This research aims to determine the use of the Canva application in making posters as a medium for learning Indonesian for class XI students at SMAN 1 Besuk. Apart from that, this research also aims to motivate teachers to be more creative and interactive in creating and using interesting learning media. This research shows that Canva is very effective in teaching poster material as a type of persuasive text. The results of this research show that using Canva can increase student creativity and learning outcomes in making posters. To analyze students' reactions to learning using this media, this research uses a descriptive qualitative approach. Data collected through observations became the basis for analyzing these findings, providing deeper insight into students' learning experiences. Overall, this research emphasizes the importance of using interactive and engaging tools such as Canva in improving students' understanding and skills in the field of poster creation.